A Clinical Study on Padabhyanga in Timira w.s.r. to Refractive Error in BAMS Students (AYUSHDHARA, 2021)
Background and Objectives: Timira, one among the Drushtigata netraroga can be compared with many disorders from refractive errors to cataract. In the present study we have compared Timira to Refractive errors which is considered as one among the avoidable blindness. Clinical features of Prathama patalagata timira is similar with the signs and symptoms of refractive errors. Padabhayanga is considered as Chakshushya and we have references in classics stating the utility of the same. With this background we have planned the work by selecting BAMS Students as the participants which will also motivate and inspire them for conducting further research. Objectives: To evaluate the therapeutic effect of Padabhyanga in the management of Timira w.s.r. to Refractive error in BAMS Students. Methods: A Randomised clinical study was taken up to scientifically validate the effects of Padabhyanga wherein 20 patients of Timira were selected. Patients were treated with Padabhyanga for 48 consecutive days. The effect of treatment was statistically analyzed using Paired student’s ‘t’–test. Results: Based on the statistical analysis Padabhyanga had better effect on all parameters thus managing the condition successfully. Interpretation & Conclusion: Padabhyanga is the effective modality of treatment which can be adopted in Timira w.s.r. to Refractive errors as a part of Dinacharya which is cost effective with minimum time duration.